2021
DOI: 10.1093/cvr/cvab081
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic alterations in a rat model of takotsubo syndrome

Abstract: Aims Cardiac energetic impairment is a major finding in takotsubo patients. We investigate specific metabolic adaptations to direct future therapies. Methods and Results An isoprenaline-injection female rat model (versus sham) was studied at day-3; recovery assessed at day-7. Substrate uptake, metabolism, inflammation and remodelling were investigated by 18F-FDG-PET, metabolomics, qPCR and WB. Isolated cardiomyocytes were pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 41 publications
3
50
0
Order By: Relevance
“…ISO significantly increased the levels of reactive oxygen species (ROS) in the setting of TTS, leading to the injury of myocardial cells, mitochondrial dysfunction, acute Ca 2+ overload, TLR4/NF-κB signaling alterations, dysregulation of the glucose and lipid metabolic pathways represented by decreases in the final glycolytic and β-oxidation metabolites and reduced availability of Krebs cycle intermediates. It was shown that icariin, an antioxidant and anti-inflammatory agent, prevented ISO-induced TTS-like cardiac dysfunction in rats by suppressing the TLR4/NF-κB pathway and long-term inhibition of PI3K/AKT/mTOR expression and by reducing the mitochondrial ROS and oxidative stress-induced apoptosis, which provides new insights into the protective effect against myocardial dysfunction in TTS rats [197][198][199][200][201].…”
Section: Animal Models and Mechanistic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…ISO significantly increased the levels of reactive oxygen species (ROS) in the setting of TTS, leading to the injury of myocardial cells, mitochondrial dysfunction, acute Ca 2+ overload, TLR4/NF-κB signaling alterations, dysregulation of the glucose and lipid metabolic pathways represented by decreases in the final glycolytic and β-oxidation metabolites and reduced availability of Krebs cycle intermediates. It was shown that icariin, an antioxidant and anti-inflammatory agent, prevented ISO-induced TTS-like cardiac dysfunction in rats by suppressing the TLR4/NF-κB pathway and long-term inhibition of PI3K/AKT/mTOR expression and by reducing the mitochondrial ROS and oxidative stress-induced apoptosis, which provides new insights into the protective effect against myocardial dysfunction in TTS rats [197][198][199][200][201].…”
Section: Animal Models and Mechanistic Studiesmentioning
confidence: 99%
“…The animal models of TTS are mainly based on monkeys, rabbits, rats and mice, which can be used to simulate TTS to a certain extent through immobilization, repeated intravenous infusion of an epinephrine overdose, vagal stimulation, intraperitoneally isoprenaline and other methods [152][153][154][182][183][184][185][186][187][188][190][191][192][193][194][195][197][198][199][200][201][202][203][204][205][206]. Many live-stranded cetaceans and terrestrial wildlife experienced capture myopathy, which was similar to TTS [207,208].…”
Section: Animal Models and Mechanistic Studiesmentioning
confidence: 99%
“…It is conceivable that a diverse variety of pathophysiologic entities (ACS, AMI, Prinzmetal’s angina, and TTS) could lead to the same pathophysiologic/pathoanatomic/pathohistologic outcome, i.e., that of “ischemic/reperfusion injury” [ 4 ], and thus therapies previously proposed for ACS and AMI [ 8 , 9 , 116 ], deserve a trial in patients with TTS [ 10 , 11 ]. Accordingly, it has been recently proposed that large doses of insulin infusions, in connection with careful monitoring to prevent hypoglycemia and hypokalemia, via concomitant infusions of dextrose and potassium supplementation, in conjunction with intravenous use of short-, or ultrashort-acting β-blockers (e.g., esmolol or landiolol) [ 39 ] ( Figure 7 ) perhaps have beneficial therapeutic effects in patients with TTS [ 10 , 11 ], addressing specifically the devastating metabolic impairment (glucose and lipid pathways dysregulation, leading to decreased final glycolytic and β-oxydation metabolites and reduced availability of Krebs intermediates), noted in TTS [ 117 , 118 ]. This proposal is based on previous literature of animal models of stress cardiomyopathy, recently summarized [ 10 ], and limited experience in patients with neurogenic cardiomyopathy and TTS [ 37 , 38 , 119 , 120 , 121 , 122 ] ( Figure 8 ).…”
Section: Future Therapeutic Options For Ttsmentioning
confidence: 99%
“…Currently, it has also been demonstrated that Takotsubo myocardium is characterized by a dysregulation of glucose and lipid metabolic pathways. In turn, this energetic deficit determines a malfunctioning Ca 2+ metabolism, inflammation, and overexpression of remodeling pathways [ 16 ]. Cotemporally, it has been shown that an increase in reactive oxygen species (ROS) followed by the downstream cascade’s effects characteristic TTS development [ 17 ], probably as a consequence of the above-mentioned dysregulation.…”
Section: New Insights Into Tts Pathophysiology: Mechanisms and Pathways From Current Evidencementioning
confidence: 99%